BIRTH PHOTOGRAPHY AS A NORMAL MATERNITY FACILITY AT PMB - Desi Latifatul Hasanah; Yanik Purwanti (Journal of Medical Genetics and Clinical Biology, 2024)
Birth photography is a new form of birth art, the emergence of birth photography as an expression of a woman's birth experience that is centered on women. Photos become a means of imaginative adventure for human experience, communication between humans and themselves, between people and even between generations. This birth memoir is a form of celebration and gift for future children, parents, or anyone else for the moment of childbirth which only happens once in a woman's life even if there are subsequent births. With current technological advances, birth documentation as a medium for capturing beautiful memories of childbirth can be easily done, using a camera or a smartphone. The data source in this study uses a literature review method which comes from several sources, both national and international journals, using published articles from Google Scholar, Radiation Oncology Journal, PubMed, and Elsevier. In this research, birth photography is used as a facility for mothers going through normal childbirth. The aim is to entice mothers to become more interested and brave in going through natural childbirth with professional midwives at PMB